A method for preparing large-size gradient structure material

Through friction stir additive manufacturing technology, the metal sheets are subjected to multiple multi-layer underwater friction stir processing, combined with the use of circulating cooling water, and the preparation of large-size gradient structure materials is realized, and the directionality of gradient structure materials in the existing technology is solved. Problems such as small size have prospects for industrial application.

CN118305550BActive Publication Date: 2025-02-14GRIMAT ENG INST CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410758738.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-13
Publication Date
2025-02-14
Estimated Expiration
2044-06-13

AI Technical Summary

Technical Problem

It is difficult to prepare large-size gradient structure materials in the prior art, and the prepared gradient structure materials have problems such as directionality, small size, and limited industrial application potential.

Method used

Friction stirring additive manufacturing technology is used to carry out multiple multi-layer underwater friction stir processing on metal sheets, and combined with the use of circulating cooling water, a temperature gradient and strain gradient are formed to achieve periodic arrangement of gradient structures in space.

Benefits of technology

The large-size gradient structure material was successfully prepared, which solved the problems of directionality and small size of gradient structure materials in traditional processes, and had industrial application prospects, and avoided cast structure defects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118305550B_ABST
    Figure CN118305550B_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a large-size gradient structure material in which gradient tissue is periodically distributed in space, and belongs to the field of gradient material preparation. The preparation method comprises the following steps: (1) preparing a metal plate, cleaning the surface of the metal plate, and the thickness of the metal plate is 5-20 mm; (2) rigidly fixing the metal plate and placing it in a water cooling tank, passing circulating cooling water, and the cooling water completely immerses the metal plate; (3) performing single-layer multi-pass underwater friction stirring processing, the stirring head needle length is 6-25 mm, and the needle length is 10%-20% greater than the thickness of the metal plate; (4) surface milling processing: performing surface milling processing on the metal plate, and the surface milling processing amount is controlled to be 0.2-1.0 mm; (5) adding a new layer of plate, repeating steps (3) and (4) until the size requirements are met; finally, mechanical processing is used to remove excess material to obtain a large-size gradient structure material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a large-size gradient structure material, and belongs to the field of gradient material preparation. Background Art

[0002] In recent years, the concept of gradient structure has been increasingly applied to engineering materials. Different from traditional homogeneous single-element materials or homogeneous single-level composite materials, gradient materials are characterized by the heterogeneity and multi-scale nature of the organization, as well as the multi-level nature of the structure. Such as grain size gradient, dislocation density gradient, twin density gradient, solid solubility gradient, phase gradient, and mixed gradient structures that combine one or more of the above. In view of the coordinated deformation effect of the gradient structure, it can have both high strength and high toughness to a certain extent, overcome the "inverted" relationship between strength and toughness in traditional materials, and greatly improve the comprehensive performance of the material.

[0003] At present, common methods for preparing gradient structures include surface mechanical grinding, ultrasonic surface rolling, plastic flow extrusion cutting, etc. However, the gradient structure prepared by surface treatment often only exists on the surface of the material. The gradient layer is very thin, and its gradient direction cannot be changed, and it cannot form a periodic distribution in space. How to prepare large-sized block components with gradient structures that are periodically distributed in space is a current research difficulty. In recent years, with the continuous development of emerging technologies, some new technologies can also be used to prepare gradient structure materials, such as direct current electrolytic deposition technology and additive manufacturing technology. The research group of Researcher Lu Lei from the Institute of Metal Research, Chinese Academy of Sciences, used direct current electrolytic deposition technology to achieve a gradient change in the thickness of the twin lamellae and the grain size along the thickness of the sample, and obtained a nano-twin copper material with a quantitatively controllable gradient structure, but its size is small and its potential for industrial application is limited. Professor Lin Xin's team at Northwestern Polytechnical University used the unique solidification cooling and thermal cycle characteristics of arc additive manufacturing technology to form a formed metal with a multi-scale grain structure and a non-uniform periodic distribution of tissue ([Zhou Y, Lin X, KangN. The heterogeneous band microstructure and mechanical performance in a wire+ arc additively manufactured 2219 al alloy. Additive Manufacturing, 2022,49: 102486]). However, this metal formed by high-energy beam additive manufacturing technology is prone to defects such as pores and cracks. These defects and the cast structure affect the contribution of the gradient structure to the mechanical properties.

[0004] Friction stir additive manufacturing is a solid-phase additive manufacturing technology developed based on the principle of friction stir. In the additive manufacturing process, since the formed metal does not melt and solidify, there will be no cast structural defects such as pores, cracks and dendrite segregation. In addition, the formed metal undergoes dynamic recrystallization under the action of thermo-mechanics to form a fine equiaxed crystal structure. By utilizing the unique temperature gradient and strain gradient in friction stir additive manufacturing and multiple stirring actions, it is expected to form a large-scale gradient structure material with a periodic arrangement of gradient structures. Summary of the invention

[0005] In view of the problems that gradient structure materials prepared by prior art have small size, gradient structure directionality and defects, the purpose of the present invention is to provide a method for preparing large-sized gradient structure materials, so as to prepare large-sized gradient structure materials with gradient tissue periodically distributed in space.

[0006] To achieve the above object, the present invention adopts the following technical solutions:

[0007] A method for preparing a large-size gradient structure material comprises the following steps:

[0008] (1) Prepare a metal sheet and clean its surface. The thickness of the metal sheet is 5 to 20 mm.

[0009] (2) Use a fixture to rigidly fix the metal plate, place the rigidly fixed metal plate in a water cooling tank, and pass circulating cooling water to completely immerse the metal plate;

[0010] (3) Single-layer multi-pass underwater friction stir processing, the stirring head shoulder diameter is 18~40 mm, the needle length is 6~25 mm, and the needle length is 10%~20% larger than the thickness of the metal sheet;

[0011] (4) Surface milling: The metal sheet after the friction stir processing in step (3) is subjected to mechanical milling to make the surface of the workpiece smooth; the surface milling amount is controlled to be 0.2~1.0 mm;

[0012] (5) Preparation of gradient structure materials: Add a new layer of plate and repeat steps (3) and (4) until the size requirements are met, thus completing the preparation of the gradient structure material blank; finally, mechanical processing is used to remove excess material to obtain a large-size gradient structure material.

[0013] Furthermore, the thickness of the metal sheet is more preferably 10-20 mm. The thicker the metal sheet is, the more significant the temperature gradient and strain gradient are, and the more obvious the organizational gradient is, during a single-pass additive manufacturing process.

[0014] Furthermore, in step (2), the temperature of the circulating cooling water is 15-25° C., and the water surface is 5-20 mm higher than the surface of the metal plate.

[0015] Furthermore, in step (3), the rotation speed of the stirring head is 400-1500 rpm, and the travel speed is 60-200 mm / min.

[0016] Furthermore, in the step (4), the surface milling amount is preferably controlled within a range of 0.3-0.8 mm. If the surface milling amount is too large, the thickness of the single-layer metal sheet will decrease.

[0017] Furthermore, in the step (5), the overlap amount of different layers of formed metal is too large, and the gradient structure is not obvious. The overlap amount of different layers of formed metal should be controlled within the range of 15% to 25%.

[0018] Furthermore, in the additive manufacturing process, since hook-shaped defects usually extend from the rear side of the stirring zone to the inside of the stirring zone, reducing the mechanical properties of the formed metal, while hook-shaped defects on the forward side extend to the outside of the stirring zone and have no effect on the mechanical properties of the formed metal, therefore, in the step (3), during the same layer of friction stir additive manufacturing, it is necessary to ensure that the forming paths of different passes are consistent, and the forward side area of ​​the latter pass covers the backward side area of ​​the previous pass, and the area prone to hook-shaped defects can be eliminated after re-stirring in the latter pass.

[0019] Furthermore, the metal sheet includes but is not limited to lightweight metals or alloys such as aluminum and magnesium. For gradient structural materials formed by heat-treatable and strengthened metals or alloys, not only can the grain size, dislocation density within the crystal, substructure, and texture characteristics be distributed in a periodic gradient along the additive manufacturing direction, but the number density of the second phase particles is also distributed in a periodic manner along the additive manufacturing direction.

[0020] Compared with the prior art, the present invention has the following advantages:

[0021] 1. The preparation method of the present invention is based on the principle of stir friction lap welding. A rigidly fixed metal sheet is subjected to multi-pass and multi-layer stir friction processing to form a block structure. During the forming process, circulating cooling water is introduced to reduce the thermal impact of the previous additive manufacturing on the next additive manufacturing, thereby ensuring the uniformity of the gradient structure material.

[0022] 2. The preparation method of the present invention utilizes the unique temperature gradient and strain gradient characteristics from high to low along the thickness direction of the stirring zone during the underwater stir friction additive manufacturing process and the overlapping area of ​​the two adjacent stirring zones undergoes re-stirring to refine the grains, thereby realizing the preparation of large-scale gradient structural materials with gradient organizations arranged periodically in space, and solving the problems of gradient structural materials prepared by traditional processes, such as directionality, small size, and limited industrial application potential.

[0023] 3. The present invention can prepare large-sized gradient structure materials and has industrial application prospects.

[0024] 4. The stir friction additive manufacturing technology involved in the present invention belongs to the solid phase processing technology. The metal material does not melt and solidify during the processing, thus avoiding the problems of cast structure defects such as pores, cracks, dendrite segregation, etc. generated in the existing gradient structure manufacturing technology. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 It is a schematic structural diagram of the tooling for underwater friction stir additive manufacturing of the present invention.

[0026] Figure 2 The cross-sectional diagram of the prepared gradient structure material. Figure 2 (a) is a schematic diagram of the macroscopic morphology of the cross section of the formed block. Figure 2 (b) Figure 2 (a) Schematic diagram of the local organization of the formed block at the heavy dashed line. Figure 2 (c) is a schematic diagram of the organization of the upper middle part of the overlap area or the non-overlap area. Figure 2 (d) is a schematic diagram of the overlapping area organization.

[0027] Figure 3 The macroscopic morphology, grain characteristics and second phase characteristics of the cross section of the gradient structure material in Example 1 are shown in FIG. Figure 3 (a) is the macroscopic morphology of the cross section of the formed block characterized by stereo microscope. Figure 3 (b) is the grain structure of the non-overlapping area characterized by EBSD. Figure 3 (c) is the grain structure diagram of the bottom of the overlap area characterized by EBSD. Figure 3 (d) is the second phase morphology of the non-overlapping area characterized by STEM. Figure 3 (e) is the morphology of the second phase at the bottom of the overlapping area characterized by STEM.

[0028] Figure 4 It is the microstructure photo of Example 2. Among them, Figure 4 (a) is the grain structure of the non-overlapping area characterized by EBSD. Figure 4 (b) is the grain structure diagram at the bottom of the overlap area characterized by EBSD.

[0029] Figure 5 It is the microstructure photo of comparative example 1. Among them, Figure 5 (a) is the grain structure of the non-overlapping area characterized by EBSD. Figure 5 (b) is the grain structure diagram at the bottom of the overlap area characterized by EBSD. DETAILED DESCRIPTION

[0030] In order to more clearly illustrate the embodiments of the present invention, the present invention is described below in conjunction with examples. The examples are only used to further illustrate the characteristics and advantages of the present invention, but the protection scope of the present invention is not limited to the following examples.

[0031] Figure 1 Schematic diagram of the structure of the underwater friction stir additive manufacturing tooling of the present invention. Figure 1 As shown, the tooling includes a cooling water trough 1, in which a forming block 7 fixed by a tooling fixture 2 is arranged, and cooling water 6 immerses the forming block 7. The forming block 7 is stirred and rubbed by a stirring head 3. The cooling water trough 1 is provided with a water inlet 4 and a water outlet 5 for input and output of circulating cooling water.

[0032] The preparation method of the large-size gradient structure material of the present invention is carried out in the following steps:

[0033] (1) Preparation of metal plates: Mechanically polish the surface of the metal plates or use alkaline washing to remove the oil and oxide film on the surface of the plates, and clean the surface of the test plates again with alcohol or acetone to prevent serious weak bonding defects in the subsequent stir friction additive manufacturing process;

[0034] (2) Rigid fixation of metal plates: Use fixtures to rigidly fix two cleaned metal plates by stacking them up and down;

[0035] (3) Passing circulating cooling water: Pass circulating cooling water into the water cooling tank with the rigidly fixed metal sheet, and the cooling water completely immerses the metal sheet to be processed;

[0036] (4) Underwater friction stir processing: Select appropriate stirring heads and process parameters to perform single-layer multi-pass underwater friction stir processing on rigidly fixed metal sheets;

[0037] (5) Surface milling: machining and milling the metal sheet after the friction stir processing in step (4) to make the processed surface of the workpiece smooth;

[0038] (6) Preparation of gradient structural materials: Add a new layer of plate and repeat steps (4) to (5) until the size requirements are met to complete the preparation of the gradient structural material blank. Finally, mechanical processing is used to remove excess material to obtain a large-size gradient structural material with a size greater than 160 mm (length) × 40 mm (width) × 40 mm (height).

[0039] Figure 2 The cross-sectional structure diagram of the gradient structure material prepared by underwater friction stir additive manufacturing technology in the present invention. Figure 2 As shown in the figure, the cross-section of the formed gradient structure material is composed of multiple stirring zones. During the single-pass friction stir processing, due to the temperature gradient and strain gradient along the thickness direction of the stirring zone, the grain size gradually decreases from the top to the bottom of the stirring zone; when a new layer of plate is added to continue forming, there is an overlapping area between two adjacent stirring zones (called the overlap zone). The metal in the overlap zone undergoes re-stirring, and the grain size is further refined. Due to the low temperature and small strain of the formed metal at the bottom of the overlap zone, the grain size is finer, the dislocation density is higher, and the number of second phases precipitated along the crystal is greater (such as Figure 2 (b) and (d)). The metal in the non-lapping zone undergoes a stirring process, resulting in a larger grain size, a lower dislocation density, and a smaller amount of second phase precipitated along the grain (e.g. Figure 2 (b) and (c)). As the height of the additive manufacturing increases, the gradient structure (grains are coarse-fine-coarse, dislocation density is few-many-few, and the number of second phases is few-many-few) is arranged periodically along the additive manufacturing direction (e.g. Figure 2 (as shown in (b)).

[0040] Example 1

[0041] A 5 mm thick 7085 aluminum alloy plate was used as the substrate. Before the test, the surface of the 7085 aluminum alloy plate was mechanically polished to remove the oil and oxide film on the surface of the plate, and the surface of the test plate was cleaned again with alcohol or acetone to prevent defects such as weak bonding during the subsequent stir friction additive manufacturing process. Then, the two processed 7085 aluminum alloy plates were rigidly fixed in the form of stacking up and down using a fixture, and circulating cooling water was passed into the water cooling tank with the rigidly fixed metal plate. The water temperature was controlled at 20°C, and the water surface was 15 mm away from the surface of the metal plate. A stirring head with a shoulder diameter of 18 mm, a needle length of 6 mm, a rotation speed of 700 rpm, and a travel speed of 160 mm / min were selected according to the process parameters. Figure 1As shown in the figure, a single-layer multi-pass underwater friction stir processing is performed. During the single-layer multi-pass friction stir processing, the travel direction of different passes is consistent, and the forward side area of ​​the stirring zone of the next pass is guaranteed to cover the backward side area of ​​the stirring zone of the previous pass. After the first layer of processing is completed, the formed metal surface is machined and milled flat, and the milling amount is 0.5 mm. After the workpiece surface is milled flat, a new layer of plate (5 mm thick 7085 aluminum alloy plate) is added, and the above process is repeated. The overlap amount of different layers is about 22%, and finally a 7085 aluminum alloy block with an effective size of length × width × height = 160 mm × 44 mm × 55 mm is obtained.

[0042] The block obtained in this embodiment was analyzed by macro and micro structure, and it was found that the formed metal had no defects, and the bottom of the overlapped position of two adjacent stirring zones was fine-grained, with high density of dislocations and substructures within the grains, and a large number of precipitated phases within the grain boundaries, while the grain size of the non-overlapping zone was large, the density of dislocations and substructures within the grains was low, and the number of precipitated phases within the grain boundaries was small (such as Figure 3 As shown). The bulk metal showed the characteristics of periodic arrangement of gradient structure along the additive manufacturing direction. The microhardness test of the bulk metal after aging at 100℃×48h along the additive manufacturing direction showed that the microhardness also showed a hard-soft-hard periodic distribution along the additive manufacturing direction. The tensile property test of the bulk metal along the additive manufacturing direction showed that after aging, the average tensile strength of the sample could reach 523 MPa.

[0043] Example 2

[0044] A 10 mm thick 7N01 aluminum alloy sheet was used as the substrate. Before the test, the surface of the 7N01 aluminum alloy sheet was mechanically polished to remove the oil and oxide film on the surface of the sheet, and the surface of the test plate was cleaned again with alcohol or acetone to prevent defects such as weak bonding during the subsequent stir friction additive manufacturing process. Then, the two processed 7N01 aluminum alloy sheets were rigidly fixed in the form of stacking up and down using a fixture, and circulating cooling water was passed into the water cooling tank with the rigidly fixed metal sheet. The water temperature was controlled at 15°C, and the water surface was 5 mm away from the surface of the metal sheet. A stirring head with a shoulder diameter of 22 mm, a needle length of 11.5 mm, a rotation speed of 1200 rpm, and a travel speed of 100 mm / min were selected according to the process parameters. Figure 1As shown in the figure, a single-layer multi-pass underwater friction stir processing is performed. During the single-layer multi-pass friction stir processing, the travel direction of different passes is consistent, and the forward side area of ​​the stirring zone of the next pass is guaranteed to cover the backward side area of ​​the stirring zone of the previous pass. After the first layer of processing is completed, the formed metal surface is machined and milled flat, and the milling amount is 0.8 mm. After the workpiece surface is milled flat, a new layer of plate (10 mm thick 7N01 aluminum alloy plate) is added, and the above process is repeated. The overlap amount of different layers is about 16%, and finally a 7N01 aluminum alloy block with an effective size of length × width × height = 200 mm × 80 mm × 50 mm is obtained.

[0045] The macro- and micro-structure analysis of the block obtained in this embodiment shows that the formed metal has no defects, and the bottom of the overlapped position of two adjacent stirring zones is a fine-grained structure, while the grain size of the non-overlapping zone is larger (such as Figure 4 As shown in the figure, the bulk metal shows the characteristics of periodic arrangement of gradient organization along the additive manufacturing direction. The microhardness test of the bulk metal after 90 days of natural aging along the additive manufacturing direction shows that the microhardness is also distributed in a hard-soft-hard periodic pattern along the additive manufacturing direction. The tensile properties of the bulk metal are tested along the additive manufacturing direction, and the results show that the average tensile strength of the sample after aging can reach 400MPa, which is higher than the tensile strength of the original parent material.

[0046] Comparative Example 1

[0047] A 3.5 mm thick 7A04 aluminum alloy sheet was used as the substrate. Before the test, the surface of the 7A04 aluminum alloy sheet was mechanically polished to remove the oil and oxide film on the surface of the sheet, and the surface of the test plate was cleaned again with alcohol or acetone to prevent defects such as weak bonding during the subsequent stir friction additive manufacturing process. Then, the two processed 7A04 aluminum alloy sheets were rigidly fixed in the form of stacking up and down using a fixture, and circulating cooling water was passed into the water cooling tank with the rigidly fixed metal sheet. The water temperature was controlled at 15°C, and the water surface was 5 mm away from the surface of the metal sheet. A stirring head with a shoulder diameter of 12.5 mm, a needle length of 4.5 mm, a rotation speed of 1200 rpm, and a travel speed of 100 mm / min were selected according to the process parameters. Figure 1Single-layer multi-pass underwater friction stir processing is performed as shown. During the single-layer multi-pass friction stir processing, the travel directions of different passes are consistent, and it is ensured that the forward side area of ​​the stirring zone of the subsequent pass covers the backward side area of ​​the stirring zone of the previous pass. After completing the first layer of processing, the formed metal surface is machined and milled, and the milling amount is 1.1 mm. After the workpiece surface is milled, a new layer of plate (3.5 mm thick 7A04 aluminum alloy plate) is added, and the above process is repeated. The overlap amount of different layers of formed metal is 42%, and finally a 7A04 aluminum alloy block is obtained. The microstructure analysis of the block obtained in this embodiment found that the grain size of the overlapping and non-overlapping areas of two adjacent stirring zones is not significantly different (such as Figure 5 As shown in the figure), the bulk metal has no obvious gradient structure characteristics.

[0048] Comparative Example 2

[0049] A 2 mm thick WE43 magnesium alloy sheet was used as the substrate. Before the test, the surface of the WE43 magnesium alloy sheet was mechanically polished to remove the oil and oxide film on the surface of the sheet, and the surface of the test plate was cleaned again with alcohol or acetone to prevent defects such as weak bonding during the subsequent stir friction additive manufacturing process. Then, the two processed WE43 magnesium alloy sheets were rigidly fixed in the form of stacking up and down using a fixture, and circulating cooling water was passed into the water cooling tank with the rigidly fixed metal sheet. The water temperature was controlled at 15°C, and the water surface was 5 mm away from the surface of the metal sheet. A stirring head with a shoulder diameter of 25 mm, a needle length of 11.5 mm, a rotation speed of 1200 rpm, and a travel speed of 100 mm / min were selected according to the process parameters. Figure 1 As shown, a single-layer multi-pass underwater friction stir processing is performed. During the single-layer multi-pass friction stir processing, the travel directions of different passes are consistent, and the forward side area of ​​the stirring zone of the next pass is guaranteed to cover the backward side area of ​​the stirring zone of the previous pass. After the first layer of processing is completed, the formed metal surface is machined and milled, and the milling amount is 0.2 mm. After the workpiece surface is milled, a new layer of plate (2 mm thick WE43 magnesium alloy plate) is added, and the above process is repeated. The overlap amount of different layers of formed metal is 15%, and finally a WE43 magnesium alloy block is obtained. The block obtained in this embodiment was subjected to microstructural analysis, and it was found that the block metal had no obvious gradient organizational characteristics.

[0050] Comparative Example 3

[0051] A 10 mm thick AZ31 magnesium alloy sheet was used as the substrate. Before the test, the surface of the AZ31 magnesium alloy sheet was mechanically polished to remove the oil and oxide film on the surface of the sheet, and the surface of the test plate was cleaned again with alcohol or acetone to prevent defects such as weak bonding during the subsequent stir friction additive manufacturing process. Then, the two processed AZ31 magnesium alloy sheets were rigidly fixed in the form of stacking up and down using a fixture, and circulating cooling water was passed into the water cooling tank with the rigidly fixed metal sheet. The water temperature was controlled at 15°C, and the water surface was 5 mm away from the surface of the metal sheet. A stirring head with a shoulder diameter of 25 mm, a needle length of 15 mm, a rotation speed of 1200 rpm, and a travel speed of 100 mm / min were selected according to the process parameters. Figure 1 As shown, a single-layer multi-pass underwater friction stir processing is performed. During the single-layer multi-pass friction stir processing, the travel directions of different passes are consistent, and the forward side area of ​​the stirring zone of the subsequent pass is guaranteed to cover the backward side area of ​​the stirring zone of the previous pass. After the first layer of processing is completed, the formed metal surface is machined and milled, and the milling amount is 0.8 mm. After the workpiece surface is milled, a new layer of plate (10 mm thick AZ31 magnesium alloy plate) is added, and the above process is repeated. The overlap amount of different layers of formed metal is 54%, and finally an AZ31 magnesium alloy block is obtained. The block obtained in this embodiment was subjected to microstructural analysis, and it was found that the gradient organizational characteristics of the block metal were not obvious.

[0052] The above is only a preferred embodiment of the present invention and does not limit the invention. It should be pointed out that for ordinary technicians in this field, under the technical enlightenment provided by the present invention, other equivalent improvements can be made, all of which can achieve the purpose of the present invention and should be regarded as the protection scope of the present invention.

Claims

1. A method for preparing a large-size gradient structure material, characterized in that: The following steps are involved: (1) Prepare aluminum alloy plates and clean the surface of the aluminum alloy plates. The thickness of the aluminum alloy plates is 10-20 mm. (2) Use a fixture to rigidly fix the aluminum alloy plate, and place the rigidly fixed aluminum alloy plate in a water cooling tank, and pass circulating cooling water to completely immerse the aluminum alloy plate; the water temperature of the circulating cooling water is 15~25℃, and the water surface is 5~20 mm higher than the surface of the aluminum alloy plate; (3) Perform single-layer multi-pass underwater friction stir processing, with the stir head shoulder diameter of 18~40 mm, the needle length of 6~25 mm, and the needle length is 10%~20% larger than the thickness of the aluminum alloy plate; (4) Surface milling: The aluminum alloy plate after the friction stir processing in step (3) is subjected to mechanical milling to make the surface of the workpiece smooth; the surface milling amount is controlled to be 0.2~1.0 mm; (5) Preparation of gradient structural materials: adding a new layer of plate, controlling the overlap between different layers of formed aluminum alloy within the range of 15% to 25%, repeating steps (3) and (4) until the size requirements are met, and completing the preparation of the gradient structural material blank; finally, mechanical processing is used to remove excess material to obtain a large-size gradient structural material; The cross-section of the formed gradient structural material is composed of multiple stirring zones. When a new layer of plate is added to continue forming, the overlapping area between two adjacent stirring zones is the overlap zone. The grain size of the formed metal at the bottom of the overlap zone is finer, the dislocation density is higher, and the number of second phases precipitated along the crystal is more. As the height of additive manufacturing increases, the non-overlapping zone-overlapping zone-non-overlapping zone in the gradient organizational structure is distributed in a periodic gradient along the additive manufacturing direction, among which the grain size is distributed in a periodic manner of coarse-fine-coarse, the dislocation density is high-low-high, and the number of second phases is small-large-small.

2. The method for preparing a large-size gradient structure material according to claim 1, characterized in that: In step (3), the rotation speed of the stirring head is 400-1500 rpm, and the travel speed is 60-200 mm / min.

3. The method for preparing a large-size gradient structure material according to claim 1, characterized in that: In the step (4), the surface milling amount is controlled within a range of 0.3 to 0.8 mm.

4. The method for preparing a large-size gradient structure material according to claim 1, characterized in that: In the step (3), during the same layer of friction stir additive manufacturing, the forming paths of different passes are ensured to be consistent, and the advancing side area of ​​the latter pass covers the retreating side area of ​​the former pass.

Citation Information

Patent Citations

  • Solid-state additive manufacturing method for large-size block ultra-fine grain metal material

    CN114571058A

  • Discontinuous gradient structure 6xxx series aluminum alloy and friction stir additive manufacturing method thereof

    CN117300327A